2017
DOI: 10.2147/ott.s134162
|View full text |Cite
|
Sign up to set email alerts
|

Combined detection of dickkopf-1 subtype classification autoantibodies as biomarkers for the diagnosis and prognosis of non-small cell lung cancer

Abstract: PurposeThis study aims to identify the clinical significance of serum autoantibodies against dickkopf-1 (DKK1) and evaluate their feasibility in the immunodiagnosis and prognosis of non-small cell lung cancer (NSCLC).Experimental designEpitope mapping by peptide microarray-based serum screening of NSCLC patients (n=72) and healthy controls (n=16) was performed. Indirect ELISA with peptides was used to measure the serum levels of autoantibodies in 206 NSCLC patients and 99 healthy controls. A 3-year follow-up w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…And followed up for 3 years. 28 Serum Dkk1 levels were quantified and analyzed in 470 patients with NSCLC (140 bone metastases, 178 extraosseous metastases and 152 complete remission). 29 Yes Yes Yes Yes Dkk1 promotes VM formation by inducing EMT-related proteins and developing CSC properties in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And followed up for 3 years. 28 Serum Dkk1 levels were quantified and analyzed in 470 patients with NSCLC (140 bone metastases, 178 extraosseous metastases and 152 complete remission). 29 Yes Yes Yes Yes Dkk1 promotes VM formation by inducing EMT-related proteins and developing CSC properties in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Shen et al 28 measured the serum levels of Dkk1 autoantibodies in 206 patients with NSCLC and 99 healthy controls by indirect ELISA. The patients were followed up for 3 years to evaluate the correlation between the serological level of antibodies and the overall survival time (OS) and progression-free survival (PFS).…”
Section: Introductionmentioning
confidence: 99%
“… 40 , 41 Various biomarkers have been explored for diagnosis, targeted therapy, or prognosis. 42 45 CXCL5 is a member of a proangiogenic subgroup of the CXC-type chemokine family. Emerging evidence has demonstrated that CXCL5 is involved in carcinogenesis and cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…43 Also, our team have confirmed the diagnostic value of DKK1 autoantibodies in non-small cell lung cancer. 44 In summary, DKK1 has been considered as a novel serologic diagnostic marker of cancer. And in some cancers, DKK1 combined with DKK1 antibodies could improve diagnostic value.…”
Section: Role In Cancer Diagnosismentioning
confidence: 99%
“…Also, their team further clarified the clinical significance of seroautoantibodies and evaluated their feasibility in immunological diagnosis and prognosis. 44 Cox regression analysis showed that anti-pepB antibody was considered as an independent prognostic factor of non-small cell lung cancer, suggesting that Pep B antibody subtype was the most valuable biomarker with good prognosis in NSCLC. Whether such unique epitopes can be found in other cancer types, and whether such a method can be used to diagnose cancer, needs further exploration.…”
Section: Application Of Dkk1 Autoantibody Detectionmentioning
confidence: 99%